DEVELOPMENT OF PHYSICAL EDUCATION IN EUROPEAN UNION: LITERATURE REVIEW - Dariusz Skalski (Pavlo Tychyna Uman State Pedagogical University, 2017)
The literature review on the development of physical education in European Union had been conducted in the article.  The author used four directions to review the literature. In order to develop Direction 1 (theoretical background to research in physical education concepts in the EU countries), a number of sources in the field of comparative pedagogical researches have been analyzed. In order to develop Direction 2 (roots and developments of physical education in the EU countries), mostly have been used historial pedagogical and philosophical researches. In order to develop Direction 3 (practical applications of the physical educa-tion concepts in the EU countries), a number of modern sources and applied researches findings have been considered. In order to develop Direction 4 (current situation in the physical training education in the EU countries), the author has analyzed a range of researches (normative documents of the European Commission, OECD analytical materials etc.).